2008
DOI: 10.1140/epjc/s10052-008-0614-6
|View full text |Cite
|
Sign up to set email alerts
|

Implicit regularization beyond one-loop order: gauge field theories

Abstract: We extend a constrained version of Implicit Regularization (CIR) beyond one loop order for gauge field theories. In this framework, the ultraviolet content of the model is displayed in terms of momentum loop integrals order by order in perturbation theory for any Feynman diagram, while the Ward-Slavnov-Taylor identities are controlled by finite surface terms. To illustrate, we apply CIR to massless abelian Gauge Field Theories (scalar and spinorial QED) to two loop order and calculate the two-loop beta-functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 42 publications
1
66
0
Order By: Relevance
“…The connection with DREG is more transparent if one uses alternatively the µ ν → 1 µν 2 or (A6) substitution and takes different values determined by the degree of divergence in each term (A3), (A4), (A5). We stress that this new regularization holds without DREG as the substitutions (20), (21) and scalar integration with a cutoff are independent of DREG. The success of both regularizations based on the property that they fulfill the consistency conditions of gauge invariance and momentum shifting.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The connection with DREG is more transparent if one uses alternatively the µ ν → 1 µν 2 or (A6) substitution and takes different values determined by the degree of divergence in each term (A3), (A4), (A5). We stress that this new regularization holds without DREG as the substitutions (20), (21) and scalar integration with a cutoff are independent of DREG. The success of both regularizations based on the property that they fulfill the consistency conditions of gauge invariance and momentum shifting.…”
Section: Discussionmentioning
confidence: 97%
“…Constrained differential renormalization is useful in supersymmetric [34] and non-Abelian gauge theories, it fulfills Slavnov-Taylor identities at one and two loops [35]. Implicit regularization [20,21] requires the same conditions as we used and it was successfully applied to the Nambu-Jona-Lasinio model [20] and to higher loop calculations in gauge theory. It was shown that the conditions guarantee gauge invariance generally and the Ward identities are fulfilled explicitly in QED at two-loop order [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations